(untitled) (International Seven Journal of Health Research, 2025)
INTRODUCTION: Pheochromocytomas are rare tumors of the chromaffin cells of the sympathetic-adrenomedullary axis, which produce catecholamines and can cause severe, sustained, or paroxysmal arterial hypertension (Lenders et al., 2005; Neumann, Young, & Eng, 2019). Clinical manifestations typically occur between the third and fourth decades of life but can occur at any age and affect both sexes equally (Bravo & Tagle, 2003). The maximum incidence is between the third and fifth decades of life, with a mean age at diagnosis of 24.9 years in hereditary cases and 43.9 years in sporadic cases (Lucena et al., 2023).